1995
DOI: 10.1002/j.1551-8833.1995.tb06437.x
|View full text |Cite
|
Sign up to set email alerts
|

DBPs in chlorinated North Carolina drinking waters

Abstract: Compliance with the proposed D/DBP Rule may be dictated to a much more significant degree by haloacetic acids than by THMs. The proposed Disinfectants/Disinfection By‐products (D/DBP) Rule establishes a maximum contaminant level (MCL) for haloacetic acids (HAAs) of 60 μg/L and revises the MCL for trihalomethanes (THMs) to 80 μg/L. In anticipation of the proposed rule, researchers obtained finished drinking water from six North Carolina utilities and analyzed for THMs, HAAs, and total organic halides. Samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 7 publications
8
75
1
1
Order By: Relevance
“…The finding of spatial variance in THM levels in the Cobb County system replicates findings of other researchers studying the distribution of THM levels in water systems using free chlorine for disinfection (3,(37)(38)(39)(40)(41). However, these findings were not expected in Corpus Christi, which uses chloramination for disinfection; after water treatment, chloramination attenuates the further production of THMs in the distribution system (17).…”
Section: Discussionsupporting
confidence: 82%
“…The finding of spatial variance in THM levels in the Cobb County system replicates findings of other researchers studying the distribution of THM levels in water systems using free chlorine for disinfection (3,(37)(38)(39)(40)(41). However, these findings were not expected in Corpus Christi, which uses chloramination for disinfection; after water treatment, chloramination attenuates the further production of THMs in the distribution system (17).…”
Section: Discussionsupporting
confidence: 82%
“…Fig. (7) shows the seasonal variations of HAA5 mean values in various individual locations of Group A and the GJA governorate of Group C. In agreement with previous studies [7,9,27,28,35], there were higher variations of HAA5 mean values in the summer compared to that in the winter as shown in Fig. (7a).…”
supporting
confidence: 89%
“…Furthermore, other studies of drinking water obtained from surface water sources reported that the highest levels among HAA components were of TCAA and DCAA [27][28][29], and the brominated ones were the lowest. In this study, the higher levels and detection frequency of MBAA relative to those found in all previous studies [21,22,[27][28][29] may be attributed to the prevalence of bromide in the source seawater. Brominated acetic acids are formed during the disinfection of water that contains bromide ions and organic matter [30,31].…”
mentioning
confidence: 86%
“…In that study, the concentration of trihalomethanes in a subject's tap water was estimated by averaging all measurements taken by the subject's community water system (hereafter referred to as the utility) during her first trimester of pregnancy. This method undoubtedly resulted in exposure misclassification, since trihalomethane levels in drinking water can vary greatly within a utility over time and distance (Symons et al, 1982;Singer et al, 1995;Lynberg et al, 2001 ), and most utilities sample only quarterly and at a limited number of locations. Furthermore, utilities oversample in areas expected to have high total trihalomethane (TTHM ) levels and often undersample in areas with low levels.…”
Section: Introductionmentioning
confidence: 99%